Handwashing Behavior Change at Scale : Evidence from a Randomized Evaluation in Vietnam - Chase, Claire; Do, Quy-Toan (World Bank, Washington, DC, 2013)
Handwashing with soap, which has been shown to reduce diarrhea in young children by as much as 48 percent, is frequently mentioned as one of the most effective and inexpensive ways to save children's lives. Yet rates of handwashing remain very low throughout the world. Handwashing with soap campaigns are de rigueur in developing countries, but little is known about their effectiveness. Few have been rigorously evaluated, and none on a large-scale. This paper evaluates a large-scale handwashing campaign in three provinces of Vietnam in 2010. Exposure to the campaign resulted in a slight increase in the availability of handwashing materials in the household, and caregivers in the treatment group were more likely to report washing hands at some of the times emphasized by the campaign. However, observed handwashing with soap at these times is low, and there isn't any difference between the treatment and control groups. As a result, no impact on health or productivity is found. These results suggest that even under seemingly optimal conditions, where knowledge and access to soap and water are not main constraints, behavior change campaigns that take place on a large scale face tradeoffs in terms of intensity and effectiveness.